STRATEGI PEMENUHAN GABAH KERING GILING (GKG) UNTUK MENCUKUPI PRODUKSI BERAS MERAH ORGANIK PT. SIRTANIO ORGANIK INDONESIA - Nurul Laili; Triana Dewi Hapsari (UPT Penerbitan Universitas Jember, 2018)
Dried Milled Grain (GKG) is produced grain by drying process with the maximum water content of 14% and ready milled into rice. Increased production of organic red rice PT. Sirtanio Organik Indonesia 2016 and 2017 wasn’t followed by an increase production of GKG as raw material for rice. In 2016 and 2017 GKG production are 127,382.75kg and 120,639.75kg. The availability of GKG hasn’t been able to meet production of organic red rice which is known that organic red rice production 2016 is 166,114.50kg and 2017 is 204,691.60kg. This study aims to find out the compliance strategies of GKG to satisfy organic red rice production. Determination of research area with purposive method that is PT. Sirtanio Organik Indonesia, Sumberbaru Village, Singojuruh, Banyuwangi. The research method used analytical method and analyzed using analytical hierarchy process (AHP). The result showed the prioritized compliance strategy of GKG to fulfill the production of organic red rice PT. Sirtanio Organik Indonesia is cooperate with other organic rice producers (0,262) regarding the availability criteria of GKP (0,591) based on raw material consideration (0,601), and others statregy as supporting. The second strategic priority is to increase the area of cultivated land by increasing number of partner farmers(0.253). The third strategic priority is to collaborate with the rice drying and grinding services(0.235). The fourth strategic priority is the use of dryer machines in grain fulfillment(0.168). The fifth strategic priority, increasing mastery of technology and SOP information(0.081).